Perubahan Jumlah Leukosit Darah Tepi Pada Kondisi Stress Penelitian Eksperimental Laboratories Pada Tikus Wistar Jantan - Enti Isnarni; Erna Sulistyani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
The leucocytes count and differential counting are routine blood test that have any significant role in diagnose and evaluation of disease or health. The aim of this study is to evaluated both in stress condition in animal model used Wistar male rat. Stress induced by electrical foot shock for 7 days. The result showed that leukocyte count in samples were higher than control (p<0.05). It was considered that stressor induce the adrenal cortex’s hormone secretion particularly glucocorticoid. This hormones caused movement of leukocyte in bone marrow storage to the vessel, leukocyte in marginating granulocyte pool moved to circulating granulocyte pool and and make the result of blood test is higher. This movement make the responds immunes to any injures worst and person with stress more susceptible to any infection.